2013
DOI: 10.1603/ec12119
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cytochrome Oxidase I Sequences for Phylogenetic Analysis and Identification of Thrips Species Occurring on Vegetable Crops

Abstract: Thrips are direct pests as well as vectors of important viruses infecting crop plants. One of the major constraints in studying the relationship between thrips vectors and tospoviruses is the difficulty of identifying the vector species because of high intraspecific variation among thrips populations. Molecular approaches have been used to identify species differences. In this study, partial cytochrome oxidase I (COI) sequences were used to understand the phylogenetic relationship among thrips populations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 42 publications
3
31
0
1
Order By: Relevance
“…viz. T. hawaiiensis and S. perseae along with previously reported cryptic species viz., T. palmi Glover et al 2010), T. tabaci (Brunner et al 2004), F. occidentalis (Rugman-Jones et al 2010), S. dorsalis Kadirvel et al 2013) based on the 'CO-I-10X barcoding Rule' proposed by Hebert et al 2004. All of them were supported by the calculated intra and inter specific genetic divergence (Table.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…viz. T. hawaiiensis and S. perseae along with previously reported cryptic species viz., T. palmi Glover et al 2010), T. tabaci (Brunner et al 2004), F. occidentalis (Rugman-Jones et al 2010), S. dorsalis Kadirvel et al 2013) based on the 'CO-I-10X barcoding Rule' proposed by Hebert et al 2004. All of them were supported by the calculated intra and inter specific genetic divergence (Table.…”
Section: Resultsmentioning
confidence: 71%
“…In this regard, DNA barcoding can be an added advantage and an effective tool for molecular species identification (Brunner et al 2004;Glover et al 2010; Lee et al 2010), elucidation of biotypes or cryptic species, and host associated genetic differences (Shufran et al 2000;Brunner et al 2004) and species discovery in insects. Additionally, DNA barcoding could also be used in the identification of unknown thrips species that co-exist in a cropping system, since one particular Tospovirus disease may sometimes be vectored by more than one species of thrips (Wijkamp et al 1995;Kadirvel et al 2013;Amin et al 1981). …”
Section: Advantages Of Dna Barcoding In Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Since Brunner et al’s [7] phylogenic analysis that identified three major genetic lineages for T. tabaci (i.e., Leek 1, Leek 2 and Tobacco strains), numerous similar analyses from around the world have followed [4], [6], [16], [17], [28]. All T. tabaci in our study were from a single leek clade that included individuals collected from an array of hosts representing seven plant families and multiple locations spanning five continents (clade number 2 in Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa spesies trips juga dilaporkan sebagai vektor virus. T. palmi dapat menularkan penyakit Groundnut bud necrosis, sementara T. tabaci Lindeman menularkan penyakit Tospovirus (Kardivel et al 2013;Fauziah & Saharan 1991).…”
Section: Pendahuluanunclassified